The influence of product quality, service quality and price on consumer purchasing decisions at colorbox cilegon center mall - Zahra, Mia Mulyani; Asfar, Andi Hasryningsih; Aribowo, Handrianto (Enrichment : Journal of Management, 2025)
The fashion retail industry is one of the sectors experiencing rapid growth in line with the increasing public awareness of trends and lifestyle. In facing increasingly intense competition, companies need to understand the factors that influence consumer purchase decisions. This study aims to analyze the influence of product quality, service quality, and price on consumer purchase decisions at Colorbox Cilegon Center Mall. The research method used is a survey method with a quantitative approach. The sample consisted of 74 respondents determined using Tabachnick and Fidell’s formula, focusing on female consumers who have made purchases at Colorbox Cilegon Center Mall. Data were analyzed using multiple linear regression with the help of SPSS Version 26. The results indicate that product quality, service quality, and price simultaneously and significantly influence purchase decisions. This is evidenced by a coefficient of determination (R²) of 85.1%, indicating that the three independent variables collectively affect purchase decisions by 85.1%. The simultaneous test shows an F-value of 133.751 (> F-table 2.736) with a significance level of 0.000 (< 0.05), indicating a significant influence of these variables on purchase decisions. These findings emphasize the importance of improving product quality, service, and competitive pricing strategies to encourage consumer purchase decisions in the fashion retail industry